“Análisis del potencial energético del estiércol de aves generada en la Granja Avícola Pujilí para la generación de energía de la empresa Incubandina ubicado en el sector de Chan cantón Pujilí provincia de Cotopaxi, 2022. Diseño de un biodigestor para la generación de biogás” - Bastidas Moreno, Cesar Gonzalo (2022)
Ecuador is one of the Latin American countries where several energies can be developed due to its geographical location, climatic behavior of the four regions, however one of the energies that has not yet been exploited is biomass, due to agricultural development, which It exists in the four regions such as the coast, the mountains, the east and the insular region where a large part of the national territory is focused on agricultural production in which poultry production rebounds in the central zone of the country, that is, the raising of posture birds and birds for then be slaughtered. That is why this project focuses on carrying out a study of the energy potential that exists in chicken manure or chicken manure, as the raw material to transform it into energy, which is a gas, in our case methane, and then into a calorific value for combustion and Finally, in electrical energy, that is why in this degree work the characterization of the chicken manure will be carried out, how much methane we can obtain from said farm and how much available energy we can have through a proposed biodigester.